Transforming the learning experience in pre-service teacher training using the flipped classroom. Issue 3 (27th May 2022) - Barahona, Camila; Nussbaum, Miguel; Espinosa, Pablo; Meneses, Alejandra; Alario-Hoyos, Carlos; Pérez-Sanagustín, Mar
ABSTRACT: The lack of information and communication technology skills among teachers is highlighted as being one of the main barriers to increasing the use of technology in teaching and learning. This study shows how technology used in a flipped classroom can improve learning among pre-service teachers, as well as boosting perceptions of their own technology skills. The students covered the instructional content before class through videos complemented by formative assessment. The data resulted in a report that the teacher then used to adapt their lecture, as well as defining the questions to be asked using an in-class response system. The responses to these questions were then discussed with the students. The results show that it is possible to change pre-service teachers' perceptions of using technology in the classroom, both as a student and as a future teacher.